(untitled) (Diametros, 2018)
This paper argues that Kant’s distinction between “civil union” (i.e., the state) and “ethical community” can be of great value in dealing with a problem that causes considerable trouble in contemporary political and social philosophy, namely the question of the normative significance and role of religion in political and social life. The first part dwells upon the third part of Kant`s Religion within the Boundaries of Mere Reason with the intention of exposing the general features of ethical community. It highlights the fact that Kant considers publicity, and indeed public authority, to be constitutive of the ethical community. The second part discusses his argument that we have a unique ethical duty to enter into an ethical community. This discussion clarifies the constitutive purpose of ethical community and sets forth why Kant thought that the ethical community should have a religious form. The third part presents an account of the constitutive purpose of the state (i.e. the political-legal community) in light of the Doctrine of Right. Throughout these steps, as is concluded, the essentials of a model for the relations between law, ethics, and religion emerge, which shows the way in which both religious and secularist worries can be met on a principled basis.